Implementation of the scramble method of cooperative learning to enhance the skill of writing Arabic sentence - Nurul Haqiqi, Latifatul Ma'rifah; Haris, Abdul; Irawan, Bambang; Maulana, Bayu Wahyu (Abjadia : International Journal of Education, 2025)
This study addresses the problem of low Arabic sentence writing skills among fifth-grade students at an elementary school in East Lombok. Contributing factors include limited writing practice and teachers’ difficulties in delivering effective and engaging writing instruction. The study aims to evaluate the implementation and effectiveness of the scramble method in improving students’ Arabic sentence writing skills on the theme of “at school.” The research employed Kurt Lewin’s Classroom Action Research (CAR) model, conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected through interviews, observations, and tests. Results showed a significant improvement in teacher performance (from 70 in Cycle I to 83.6 in Cycle II) and student activity (from 72 to 85). Writing skills also increased, with the average class score rising from 65.69 to 83, and the mastery level improving from 46.15% to 84.61%. These findings highlight the effectiveness of the scramble method in enhancing Arabic writing instruction at the primary level and recommend its broader application in similar contexts.